Tissue doppler imaging in thalassemia major patients: correlation between systolic and diastolic function with serum ferritin level - Syarif Rohimi; Najib Advani; Sudigdo Sastroasmoro; Bambang Mardiyono; Sukman Tulus Putra; Mulyadi M. Djer; Fajar Subroto (Indonesian Pediatric Society Publishing House, 2012)
Background Thalassemia is a major public health problem in Indonesia. Cardiac diseases remain as the main cause of death in these patients due to iron overload. Although the T2* magnetic resonance imaging has been considered as the gold standard for assessing cardiac iron overload but it has limited availability. The tissue doppler imaging (TDI) echocardiography, a fairly new and easy method that is suggested, can detect early abnormal myocardial iron overload. Objective To assess myocardial systolic and diastolic function of thalassemic patients using TDI and examine their correlation with serum ferritin level. Methods A cross􀁌sectional study was conducted from January to March 2011 at the Harapan Kita Women and Children Hospital. We performed clinical examination, serum ferritin level, as well as conventional and tissue doppler echocardiography on all subjects. Results We included 34 regularly􀁌tranfused patients, of which 17 were boys. The mean age of the subjects was 11.6 (SD 4.7 years, range 2.6 􀁌 20 years). Mean pulse rate and blood pressure were within normal range. Hemoglobin level at inclusion ranged from 5.8 to 6 g/dL. Almost all patients did not receive regular chelation therapy. Median serum ferritin level was 6275 ng/mL (range 2151 - 17,646 ng/mL). Conventional echocardiography showed normal systolic function, but some diastolic dysfunctions were found including E wave abnormalites in 4 patients, A wave abnormalites in 3, and E/A ratio abnormalites found in 3. The TDI showed decreased systolic function (Sa wave abnormality) in 9 patients and diastolic dysfunctions (Ea wave abnormality in 11 patients and Aa wave abnormaly in 2). No abnormality was found in Ea/Aa and ElEa ratios. There was a weak negative correlation between ferritin level and Sa wave and Ea wave respectively and a moderately negative correlation between ferritin level and Ea/ Aa ratio. There was no correlation between serum ferritin and Aa wave or ElEa ratio. Conclusion TDI identifies a greater number of patients Mth systolic and diastolic myocardial dysfunction than was revealed by conventional echocardiography. There was a weak negative correlation between serum ferritin to Sa wave and Ea wave, and a moderately negative correlation between ferritin and Ea/Aa ratio. There was no correlation between serum ferritin and Aa wave or ElEa ratio. [paediatr Indones. 2012;52:187,93].